ChemInform Abstract: Emerging Targets in Photopharmacology. Issue 44 (13th October 2016) - Lerch, Michael M.; Hansen, Mickel J.; van Dam, Gooitzen M.; Szymanski, Wiktor; Feringa, Ben L.
Abstract: Review: 184 refs.